The application of BIM technology in variation control of construction material of expressway asphalt pavement under machine vision. (14th July 2022) - Sun, Hanyao
In order to improve the working life and service quality of asphalt pavement, this study uses building information modelling (BIM) technology to monitor the screening of asphalt mixtures and uses machine vision to study the composite grading of aggregates. At the same time, BIM technology is used to estimate the permanent deformation and fatigue life of the asphalt mixture layer. The results show that the gradation, oil-stone ratio, gradation segregation and temperature segregation in the mixing process of the asphalt mixture all have an effect on the performance of the asphalt mixture. The use of BIM technology improves the accuracy of the composite gradation ratio and can accurately predict the fatigue life of the asphalt mixture layer. Therefore, the use of BIM technology greatly facilitates the study of material variability in asphalt pavement construction and is more conducive to relevant personnel to make reasonable construction decisions.